Attitude towards sex: study of secondary schoolchildren in Selangor state - Abdullah, Maha; Gyanchand Rampal, Lekhraj Rampal; Md Zain, Azhar; Mohd Sidik, Sherina; Vidyadaran, Sharmili; Abdah, A.; Ramasamy, Rajesh; Sekawi, Zamberi; Loong, Yik Yee; Awang, Hamidin; Abdul Rahim, Firdaus; Abdul Aziz, Ahmad Fazli; et al. (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2010)
Introduction: HIV/AIDS is one of the leading health problems worldwide. There is an increasing rate among the ages between 13 to 49 years old. School based intervention is an important component of community-based interventions for HIV/AIDS and is the best stage to promote abstinence which is best maintained among those not sexually experienced. Objectives: This study was carried out to determine attitude towards sex among secondary school children in Selangor state. Methods: A cross-sectional study design was used. Four out of nine districts in Selangor state were selected at random. Students were divided according to gender, academic performance (good or poor) with no behavioural problems and students with evidence of behaviour problems (at risk). Results: Out of 149 students, the majority (56.4%) were females. The majority of students did not think sex should be discussed in depth and do not speak to parents, teachers, religious teachers, counselors, relatives, doctors or nurses but speak to friends regarding sex. More than half watch pornography. A significantly higher percentage of male students in the weak and at-risk group admit to thinking of intimacy (hugging and kissing) with the opposite gender. A higher number of these students would try sex out of curiosity, for fun, because it was difficult to say ‘no’ to and that they would like it. A significantly higher percentage will try sex because they did not want to hurt their girlfriends’ feeling by saying ‘no’. While the majority of students think intimacy will end in sex, a significantly higher percentage of male at-risk students think just talking with the opposite gender will end in sex. The majority of male students responded feeling attracted to the picture of a girl in sexy clothing but a significantly higher percentage of at-risk students also felt attracted to the picture of a girl properly attired. A significantly higher percentage of male at-risk students say parents do not say sex before marriage is wrong and a significantly higher percentage of male students of weak and at-risk groups say girlfriends say sex before marriage is okay. A significantly higher percentage of weak and at-risk students speak to doctors regarding sex and think sex should be discussed in depth. Conclusion: Weak and at-risk male students appeared to have a more vulnerable attitude towards sex. This may predispose them to risky sexual behaviours leading to HIV/AIDS. Poor academic performance and behaviour problems may not be different as potential sexual risk predictors. The information obtained will be useful in designing intervention programmes in the prevention of HIV/AIDS.